Student Engagement and Academic Achievement through STAD Cooperative Learning Integrated with Interactive Multimedia - Nur, Sri Mukminati; Syam Pratomo, Ryan Humardani (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
In this quantitative study, students in class XI IPA 1, who were taught with the STAD cooperative learning model, achieved an average performance classified as “very good.” In contrast, the control group, class XI IPA 2, recorded a slightly lower average. The normality test confirmed that the data distribution satisfied the normality assumption because its significance level surpassed the standard threshold. The homogeneity test likewise demonstrated uniform variances between the two groups, making them homogeneous. During hypothesis testing, the significance level remained above the rejection boundary, and the calculated t‑value fell below the critical value, leading to the acceptance of the null hypothesis. Consequently, the use of the STAD model, even when supported by interactive multimedia, did not significantly influence student engagement at SMAN 14 Gowa.